SUPERVISION OF KPPU ON THE ACTION OF MERGERS DONE BY MINING COMPANIES - Preeti Kartika Putri; Paramita Prananingtyas (Fakultas Hukum, Universitas Diponegoro, 2020)
Mining companies conduct mergers to ensure and strengthen their position in their relevant market. Mining company mergers that aren’t supervised can result in monopoly and unfair business practices. The issue discussed is the supervision of mergers for mining companies by KPPU. This is a normative juridical research through a statutory and conceptual approach. The result indicates that mining companies are subject to legal provisions of limited liability company and competition law.There is no regulations regarding mergers in Indonesian mining law.Supervision of said mergers by KPPU can be carried out by voluntary consultation or by obligatory post merger notification. The scope of KPPU's supervision also includes mining companies’ compliances in case of notification. Delay of such notification will be examined by KPPU and subsequently fined if proven to have committed violation. However, post merger notification is only adopted by only a few countries for it is considered no longer guarantee legal certainty.